Review on Gastroretentive Systems for Olmesartan Medoxomil - Hursh Gupta; Manmohan Sharma; Anil Ahuja; Shashank Tiwari (Asian Journal of Pharmaceutical Research and Development, 2025)
Olmesartan Medoxomil, an angiotensin receptor blocker, is widely used to treat hypertension and cardiovascular diseases but suffers from low bioavailability, short half-life, and frequent dosing requirements. Gastroretentive drug delivery systems (GRDDS) offer a promising solution by prolonging gastric residence, improving solubility, and enhancing absorption. This review explores various GRDDS strategies suitable for Olmesartan Medoxomil, including floating, swelling, mucoadhesive, high-density, and magnetic systems. It discusses the polymers and excipients involved, such as hydrophilic polymers (HPMC, sodium alginate), hydrophobic polymers (ethyl cellulose), gas-generating agents, and density enhancers. Mechanisms like buoyancy, swelling, mucoadhesion, sedimentation, and magnetic localization are elaborated to explain their role in enhancing retention. Evaluation parameters like floating lag time, swelling index, and drug release kinetics are also summarized. The review highlights formulation challenges and suggests future directions, including smart polymers, nanocarriers, and personalized medicine, aimed at improving therapeutic efficacy and patient compliance.